2021
DOI: 10.1038/s41467-021-23313-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition mechanism of SARS-CoV-2 main protease by ebselen and its derivatives

Abstract: The SARS-CoV-2 pandemic has triggered global efforts to develop therapeutics. The main protease of SARS-CoV-2 (Mpro), critical for viral replication, is a key target for therapeutic development. An organoselenium drug called ebselen has been demonstrated to have potent Mpro inhibition and antiviral activity. We have examined the binding modes of ebselen and its derivative in Mpro via high resolution co-crystallography and investigated their chemical reactivity via mass spectrometry. Stronger Mpro inhibition th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
190
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(203 citation statements)
references
References 33 publications
11
190
1
1
Order By: Relevance
“… N.A. Not a M pro inhibitor Hits from drug repurposing Calpain inhibitor II 0.97 ± 0.27 2 8.98 ± 2.0 26 6.65 2 >60 0.60 ± 0.11 2.07 ± 0.76 2 27 ± 1.4 26 6XA4 3 Validated M pro Inhibitor Cell-type dependent Calpain inhibitor XII 0.45 ± 0.06 2 6.48 ± 3.4 26 7.86 2 38.71 ± 5.66 0.79 ± 0.10 0.49 ± 0.18 2 1.3 ± 0.57 26 6XBH 3 Validated M pro Inhibitor Cell-type dependent Ebselen >60 41 0.67 ± 0.09 16 , 42 >100 26 0.14 41 >60 >60 4.67 ± 0.80 16 , 42 >100 26 7BAK 42 Not a M pro inhibitor Disulfiram >60 41 9.35 ± 0.18 16 0.21 41 >60 >240 not active 16 N.A. Not a M pro inhibitor Carmofur 28.2 ± 9.5 41 1.82 ± 0.06 16 >1...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… N.A. Not a M pro inhibitor Hits from drug repurposing Calpain inhibitor II 0.97 ± 0.27 2 8.98 ± 2.0 26 6.65 2 >60 0.60 ± 0.11 2.07 ± 0.76 2 27 ± 1.4 26 6XA4 3 Validated M pro Inhibitor Cell-type dependent Calpain inhibitor XII 0.45 ± 0.06 2 6.48 ± 3.4 26 7.86 2 38.71 ± 5.66 0.79 ± 0.10 0.49 ± 0.18 2 1.3 ± 0.57 26 6XBH 3 Validated M pro Inhibitor Cell-type dependent Ebselen >60 41 0.67 ± 0.09 16 , 42 >100 26 0.14 41 >60 >60 4.67 ± 0.80 16 , 42 >100 26 7BAK 42 Not a M pro inhibitor Disulfiram >60 41 9.35 ± 0.18 16 0.21 41 >60 >240 not active 16 N.A. Not a M pro inhibitor Carmofur 28.2 ± 9.5 41 1.82 ± 0.06 16 >1...…”
Section: Resultsmentioning
confidence: 99%
“…Despite the accumulating evidence to support the promiscuous mechanism of action of ebselen, several studies continue to explore ebselen and its analogs as SARS-CoV-2 M pro and PL pro inhibitors 42 , 61 , 62 . A number of ebselen analogs were designed and found to have comparable enzymatic inhibition and antiviral activity as ebselen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding is further stabilized by a hydrogen bond between the carbonyl oxygen atom of ebselen and Glu 166. These results are consistent with a recently reported crystal structure of SARS-CoV-2 M pro in complex with ebselen, which indicates that it primarily binds to the catalytic site of the enzyme and forms a selenyl sulfide bond with Cys 145; this was further confirmed by LC/MRM-MS. 24 …”
Section: Resultsmentioning
confidence: 99%
“…At the time the present review article was almost complete, a very important paper was published by Yang and coworkers who, in an attempt to obtain co-crystal structures between ebselen, its analogues and M pro , found that after protein/small molecule incubation only the selenium atom is present in the enzyme active site, suggesting the mechanism summarized in Scheme 5 . In particular, once the selenenyl sulfide intermediate is formed, it reacts through a SNAr-like mechanism with water, leading to the formation of 2-hydroxy- N -phenylbenzamide and the selenenylated Cys145 [ 54 ].…”
Section: Antimicrobial Activitiesmentioning
confidence: 99%